An LC‐MS/MS method for simultaneous determination of cefprozil diastereomers in human plasma and its application for the bioequivalence study of two cefprozil tablets in healthy Chinese volunteers. (27th August 2015) - Liu, Min; Ma, Jing‐Yi; Zhang, Yanan; Wang, Xiaolin; Zhao, Hongna; Du, Aihua; Yang, Man; Meng, Lingjie; Deng, Ming; Liu, Huichen
Abstract: A rapid and sensitive liquid chromatography–tandem mass spectrometric method was developed for the first time and validated for the determination of cefprozil diastereomers in human plasma. The plasma samples were prepared by protein precipitation using acetonitrile. Detection was performed using an electronic spray ion source in the negative ion mode, operating in the multiple reaction monitoring of the transitions m / z 388.0 to m / z 205.0 for cefprozil diastereomers and m / z 346.1 to m / z 268.1 for cephalexin (the internal standard). The calibration curves of cis ‐cefprozil and trans ‐cefprozil were linear in the ranges 0.125–16.0 µg/mL and 0.0403–1.72 µg/mL, respectively. The lower limits of quantification of cis ‐ and trans ‐cefprozil were 0.125 and 0.0403 µg/mL in human plasma, respectively. The intra‐ and inter‐day precisions of cis ‐ and trans ‐cefprozil were all <9.7%, and the accuracy ranged from 99.2 to 104.7% and from 100.6 to 102.2%, respectively. The validated method was successfully applied to a bioequivalence study of two cefprozil formulations in 24 healthy Chinese volunteers. The two cefprozil tablets were bioequivalent by measurement of cis ‐, trans ‐ and total cefprozil. We suggest that the bioequivalence of cefprozil formulations can be evaluated only using cis ‐cefprozil as the analyte in future studies. Copyright © 2015 John Wiley & Sons, Ltd.